Use of nitic oxide donor isosorbide mononitrate for fre-induction cervical ripening: a randomized controlled trial. - Rameez, M.F.M (My University, 2005)
The objective was determin wliether sustained release Isosorblde monomtrate (ISMN) 60mg administered vaginally is effective for pre induction cervical ripening. A double blind randomised controlled trial carried out at the University Obstetrics Unit, Galle, Sri Lanka for a period of nine months. One hundred and fifty six women with uncomplicated singleton pregnancies at 41 weeks of gestation with a modified Bishops score (MBS) 5 were allocated by stratified ( primip/ multip) block randomisation to receive either ISMN 60mg (n